2006
DOI: 10.7589/0090-3558-42.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Mongolian gazelles (Procapra gutturosa) to foot and mouth disease virus

Abstract: ABSTRACT:Foot and mouth disease is a highly contagious acute viral disease that affects most ruminant and porcine species. During 2001, 33 serum samples were collected from Mongolian gazelles (Procapra gutturosa) in the Eastern Steppe of Mongolia. Samples were tested for antibodies to seven subtypes of foot-andmouth-disease virus (FMDV). Antibodies were detected in 67% of the animals, and serologic results indicated exposure to FMDV-O. This virus was present in domestic animal populations in Mongolia from 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Furthermore, managed systems are often highly productive, thereby providing abundant resources that may be used by non-agricultural species (Westphal et al, 2003). Knobel et al (2008) pathogen Ethiopia Rabies virus generalist Lembo et al (2008) pathogen Ethiopia Rabies virus generalist Lipa and Triggiani (1988) pathogen Canada Crithidia bombi specialist Nyamsuren et al (2006) pathogen Mongolia Foot and Mouth disease generalist Otterstatter and Thomson (2007) pathogen Canada Crithidia bombi specialist Sillero-Zubiri et al (1996) pathogen Ethiopia Rabies virus generalist Aizen and Feinsinger (1994a) pollinator Argentina Apis mellifera generalist Aizen and Feinsinger, 1994b pollinator Argentina Apis spp. generalist Holzschuh et al (2011) pollinator Germany Bombus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, managed systems are often highly productive, thereby providing abundant resources that may be used by non-agricultural species (Westphal et al, 2003). Knobel et al (2008) pathogen Ethiopia Rabies virus generalist Lembo et al (2008) pathogen Ethiopia Rabies virus generalist Lipa and Triggiani (1988) pathogen Canada Crithidia bombi specialist Nyamsuren et al (2006) pathogen Mongolia Foot and Mouth disease generalist Otterstatter and Thomson (2007) pathogen Canada Crithidia bombi specialist Sillero-Zubiri et al (1996) pathogen Ethiopia Rabies virus generalist Aizen and Feinsinger (1994a) pollinator Argentina Apis mellifera generalist Aizen and Feinsinger, 1994b pollinator Argentina Apis spp. generalist Holzschuh et al (2011) pollinator Germany Bombus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Lembo et al (2008) adds evidence to the spillover argument by showing that the reservoir of rabies in the Serengeti ecosystem is a complex multi-host community where domestic dogs are the only population essential for persistence, although other carnivores contribute to the reservoir as non-maintenance populations. After a 2000-2002 foot and mouth disease outbreak in domestic livestock in Mongolia, a study in 2001 found the disease in over half of the Mongolian gazelles sampled and authors believe spillover of the virus from domestic animals was the likely cause of the outbreak (Nyamsuren et al, 2006).…”
Section: Spillover From Managed To Natural Systemsmentioning
confidence: 99%
“…Mongolian gazelles are known to carry foot-and-mouth viruses east of the range of P. picticaudata; 67% of 33 gazelles had positive antibody tests to 7 subtypes of footand-mouth disease (Nyamsuren et al 2006). In the past, such exposure has caused significant mortality of Mongolian gazelles that form herds in the thousands (Sokolov and Lushchekina 1997), but similar events have not been reported for P. picticaudata, which does not aggregate into large herds (D. Mallon, pers.…”
Section: Ecologymentioning
confidence: 99%
“…Related Mongolian gazelles are known to carry foot-and-mouth viruses east of the range of P. przewalskii; 67% of 33 gazelles had positive antibody tests to 7 subtypes of foot-and-mouth disease (Nyamsuren et al 2006). Such exposure has caused significant mortality of Mongolian gazelles in the past (Sokolov and Lushchekina 1997) and theoretically poses a threat to P. przewalskii.…”
Section: Ecologymentioning
confidence: 99%